Study of the hondo (kyakuden, WO) of Rinzai Zen Sect Buddhist Temples in Kyoto,in the Early Edo Period (1596-1681). The Development and Changes in the Typical Plans of the Sanctuary and Veranda. - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Magister Manajemen UGM, 2001)
In the early part of the Edo period, from Keicheo 1 (1596) to Enpeo 9 (1681) the number of Rinzai Zen sect tacchils (memorial cloisters) in KyOto increased. The sanctuary and veranda of several memorial cloisters were reformed. On the basis of restoration, the purposes of this study will attempt to clarify the developments and changes in the typical plans of memorial cloisters, during the early part of the Edo period. From the restoration plans, it is possible to deduce the reasons for change and trace the various development. Previously, the other studies has been conducted, as seen at references is form of the resultant reconstruction plans of sanctuary and veranda in the mid-Edo period, from Genroku 6 (1693) to Kansei 9 (1797), and in the late Edo period, from Bunka 4 (1807) to Kaei 7 (1854). The interrelated both of these studies is to know the development and changes of type of plans of sanctuary and veranda during the Edo period (1596-1868). The development and change of the sanctuary appeared from the early Edo period until the mid-Edo period. The reason for this is a need to accommodate the placement of carved statues of the cloisters founders. Based on the arrangements of verandas, it is evident that the placement of a 1 ken veranda at the left or right sides of a building was related to the fixed of the entrance hall and temple kitchen. Further more, most of the sayanoma encompass remnants of the 1 ken veranda. The reason for the change was to redefine the veranda's function as a resting area during religious services.